“A Free Republic, Like Our Own”: The US Navy and the African Colonization Movement in Public Discourse, 1819-60 - Bailey, Roger A. (The Northern Mariner / Le marin du nord)

(untitled) (Canadian Nautical Research Society and North American Society for Oceanic History, 2025)
This article examines how US naval officers’ attitudes about slavery, race, and American empire led many to support for America’s African colonization movement in the antebellum era. It argues that beyond the well-documented support they provided in Africa, many American naval officers joined colonization societies, gave speeches, published in newspapers, and authored books to advocate for colonization in the United States. Drawing on their firsthand experience, they provided credibility to the movement at a time when it was sorely needed in response to attacks from both sides of the political spectrum.